Estudos difratométricos do polimorfismo do Bi2O3 dopado com terras raras - Machado, Carla Fabiana Cerqueira (2013)
In the present investigation compounds based on Bi2O3, those of nominal composition Bi1-x_RExO1,5, (with TR =Yb, Gd, Eu and Nd) and, also, the Bi12MO20 cubic sillenites (with M= Al, Si, Ti, Ga and Fe), were synthesized by high-energy milling, followed by thermal annealing and quenching to room temperature. The compounds prepared were structurally characterized by X-ray diffractometry, refining the diffractograms by the Rietveld method. The aim was to investigate the structural behavior of these systems, varying the doping rare earth and its concentration in the 0.05 _ x _ 0.75 range, besides the nature of M in the case of sillenites. It was verified for the Bi1-xTRxO1.5 system that a single tetragonal phase was stabilized for the x = 0.5 concentration, but others, cubic and rhombohedral phases, are formed when the concentration increases until reach a solubility limit, beyond which the precursor oxide RE2O3 remains un-reacted. Regarding the sillenites, in general this system also presented the formation of secondary phases as the rare earth doping level increased. For M = Ti, a higher tendency to maintain the cubic sillenite as a single phase was verified, which was attributed to the substitution of bismuth by the rare earth, in the crystal lattice. For both systems studied, the results obtained are discussed in terms of the ionic radii of the rare earth cations and of the types of lattice sites occupied by the bismuth cation.